Hygrothermal behaviour of hemp-lime walls: the effect of binder carbonation over time. (1st April 2023) - Moletti, C.; Aversa, P.; Losini, A.E.; Dotelli, G.; Woloszyn, M.; Luprano, V.A.M.
Abstract: Bio-based building materials are produced by recovering agricultural biomasses which are used as vegetal aggregate to replace traditional ones and realize more sustainable building materials. This study focuses on hemp-lime that is made by mixing a lime-based binder with hemp shives i.e. the waste of industrial hemp cultivation. The work aims to evaluate the effect of the maturation of hemp-lime on its hygrothermal performances. Specifically, the binder undergoes carbonation reaction through which the strength of the material and its hygrothermal properties develop. With this aim, two experimental campaigns were carried out on an experimental wall built using prefabricated hemp-lime blocks: the first few months after the construction and the second one after 3 years. The wall, equipped with hygrothermal sensors, was subjected to cycles at varying relative humidity values and fixed temperatures applied with the help of a climatic chamber. The cycles were performed at 23 °C and 35 °C to focus on the performances of the material in conditions comparable to those of the Mediterranean climate. The results prove that hygrothermal performances improve with maturation, which could be due to the carbonation of the binder and to the reduction of the initial moisture content. Numerical simulations of the experimental tests were implemented using the software WUFI® aiming at confirming the experimental methodology and also the possibility of simulating the behavior of such innovative material in dynamic regime. The proceeding of carbonation was proved through X-ray diffraction (XRD) and thermogravimetric (TG-DTG) analyses of samples having different maturation times. Highlights: Hygrothermal tests on a hemp-lime experimental wall. Microstructural characterization to investigate hemp-lime carbonation. Comparison between the performances of fresh and matured material. Numerical simulation of hemp-lime behavior in dynamic regime. Focus on Mediterranean climatic conditions.